The Change of the Concept of Poetry in Vasko Popa’s Later Collections - Vladušić, Slobodan V. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The text starts from the fact that literary critics tend to disregard Vasko Popa’s later poetry collections – Živo meso (1975), Kuća nasred druma (1975), and Rez (1981) – thus implicitly or explicitly denying their value. This paper aims to prove that in the given poetry collections there exists a change in the concept of poetry, rather than a mere poetic transformation inside the same concept of modern poetry. First trait of this new poetry concept is the repersonalization of the poetic act, which requires the introduction of the poetic subject (instead of the lyrical subject). The poetic subject of this kind of poetry, does not, however, have anything in common with the Romantic poetic subject, because the issue is not the separation of the subject from the collective of its contemporaries, as was the case in Romanticism. Quite the contrary. So as to understand this shift in the poetic concept, we used the term “personality.” We defend the thesis that Popa, in his three poetry collections all published in the same year of 1975 (Vučija so, Živo meso, Kuća nasred druma) wanted to demonstrate three spheres of personality: mythical, personal, and collectively-political. In the same way, we tried to show that Popa’s poems from the collection Živo meso ought to be read as elements of an experience that is made into a life story of personality, not merely as aesthetical objects independent of any kind of personalization.